P78 Measuring maternal mood. (2nd September 2017) - Savage-McGlynn, E; Redshaw, M; Martin, C
Abstract : Background: Mood disorders are common among women during the perinatal period, impacting their well-being and that of their families. Prevalence estimates range from 8 to upwards of 40%. Variable detection of cases has been attributed to different measures used, timing of assessment, women not disclosing their feelings, and health professionals not asking questions in meaningful ways. Different measures have been used along the maternity care pathway, with varying reliability and specificity to detect cases and commonly employ graded multiple response format. Listening to what women say about completing such measures, there is a clear need to develop alternative methods of assessing maternal mood in the perinatal period. Objective: To develop a measure of maternal mood that provides novel answering and scoring formats, accounts for the spectrum of emotions and symptoms experienced by women in the perinatal period, and correlates with clinical diagnostic measures. Methods: A literature review was conducted to assess current understanding of diagnostic criteria for perinatal mental health conditions. Based on previous research with adjective checklists and women's free text responses to national maternity surveys in 2010 and 2014, scoping of the measure was undertaken. A list of 24 adjectives (12 positive items, 12 negative items) was determined for a prototype measure in which women could choose the adjectives to describe how they had been feeling in the last seven days. Cognitive interviews were conducted with 12 women who had recently given birth, and positive feedback endorsed the content, verified item selection and face validity of the scale. Results: The checklist was administered in a survey of maternal and child health to which 551 new mothers responded. Exploratory and Confirmatory factor analyses were conducted to explore underlying factor structure. Two models resulted: a two-factor solution (1. positive mood, 2. negative mood) and a four-factor solution: (1. positive mood, 2. negative mood, agitation; 3.anhedonia, low energy; 4. positive life orientation). Analyses were undertaken for validation and to explore associations with other screening measures to support its use. Conclusion: This novel method of reporting feelings and mood in an engaging format will facilitate research in the perinatal field and allow more opportunities for conversations about mood and mental health with health care professionals. As a tool that is psychometrically robust, time-efficient, and which may afford greater insight on the emotional state of the women cared for, the perinatal mood checklist is an effective addition to measures currently available.